Assessment and documentation in early childhood education - Alasuutari, Maarit; Markström, Ann-Marie, 1956-; Vallberg Roth, Ann-Christine, 1960- (Routledge, 2014)
"Documentation in early childhood education is typically seen as a means to enhance the quality of care and education, and as a way to take account of the child's view. This timely book considers the increasing trend towards systematic child documentation especially in early childhood institutions. The authors present ways in which assessment and evaluation is done sometimes explicitly but more often implicitly in these practices, and explore their means, aims, forms, and functions. They also examine the rationalities of child documentation from the perspective of professional practice and professionalism and suggest that documentation and assessment practices can weaken and constrain but also empower and strengthen teachers, children and parents"--Resumé vydavatele
Keywords: děti; základní vzdělávání -- Skandinávie; předškolní výchova -- Skandinávie; pedagogická evaluace -- Skandinávie; children; elementary school education -- Scandinavia; preschool education -- Scandinavia; educational evaluation -- Scandinavia; studie; studies